Tecnologia per il web learning Realtà e scenari - Delogu, Cristina (Strumenti per la didattica e la ricerca, 2007)
This book maps out a course through the methodological and technological innovations of internet-based training, setting the emphasis on the collaborative character of experiences of learning and on the interactivity of the virtual workshops. On the one hand, this underscores the possibilities offered by the net to make available educational modes centred on the social process that enables learning in an active manner, rather than on the centrality of contents to be passively transferred to the students. On the other hand, it also shows how in the virtual workshops it is possible to develop one's understanding of the phenomena that are the subject of learning as a result of the interaction with the phenomena themselves, reproduced in the computer, acting upon them and observing the consequences of one's own actions. The effect is to underline how this type of model of learning can help to overcome the technology gap between different countries and social groups (the digital divide) and also to make learning more accessible even to disabled students.